The Role of Village Apparatus in Managing Village Assets Based on the Regulation of the Minister of Home Affairs Number 1 of 2016 - Fitriani Hakim; Siti Ngainnur Rohmah (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
Village officials play an important role in managing village assets because they are assets owned by the village, although in managing village assets still have certain limitations, especially in the organization of government. This paper provides an understanding of how village asset management is based on Permendagri Number 1 of 2016 and how the role of langonsari village apparatus, Pameungpeuk District, Bandung Regency in managing village assets. This research is a qualitative research. The data collection technique was carried out by means of field research, using observation methods, and interviews with the Village Head, Village Secretary and several representatives of village officials in Langonsari Village, Pameungpeuk District, Bandung Regency, totaling 5 informants. The results showed that the role of village officials in managing village assets has not gone well, so that the results are not optimal in managing the village's assets. In addition, there are also obstacles such as lack of HR competence and village officials who do not know the specifics of village asset management which greatly affects the implementation in the utilization or management process. Which causes the implementation of village asset management in Langonsari Village has not been in accordance with the regulation of permendagri Number 1 of 2016 concerning Village Asset Management.